Factor that influence attitude towards viral marketing among Generation Y / Ezatul Hasanah Jaidon - Jaidon, Ezatul Hasanah (Faculty of Business and Management, 2019)
The rapid growth of internet and the use of e-commerce have made viral marketing an appealing marketing method for most firms and marketers in order to promote and advertise their products or services. However, before involving with viral marketing, firms and marketers need to learn and recognize whether the customers will react positively or negatively towards it. Thus, it is important for firms and marketers to understand the factor that influence customer’s attitude towards viral marketing. In this research study, the purpose is to investigate and examine whether the factor of informativeness, entertainment, source credibility, and irritation will affect attitude towards viral marketing. This study was conducted to focus on the customer in Johor, Malaysia. In addition, it was mainly targeted to the people of Generation Y which is those who were born between the age of 1981 and 2000. Based on the results that have been retrieved in this study, it was found that the independent variable of source credibility has a significant relationship with the dependent variable of attitude towards viral marketing. While, the other independent variables which is informativeness, entertainment and irritation is found to have no significant effect on attitude towards viral marketing.